THE IMPORTANCE OF IMPROVING POPULATION HEALTH - Arofat Tukhtamuratovna Shorakhimova, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Improving the general health of the population is one of the key tasks of modern healthcare systems. It includes both medical measures and the creation of favorable conditions for work and life, recreation and physical education, the organization of healthy and nutritious nutrition for various groups, environmental improvement, and the improvement of well-being and living conditions of the population.